2009
DOI: 10.1097/nmd.0b013e3181a61f52
|View full text |Cite
|
Sign up to set email alerts
|

The Test of Self-Conscious Affect-3 in Japanese University Students

Abstract: The psychometric properties of the Japanese Test of Self-Conscious Affect-3 (TOSCA-3), a self-report measure of self-conscious emotions, were examined in Japanese university students. Confirmatory factor analyses showed good fits of the theory-driven model for 6 emotions to the data. The subscales of the TOSCA-3 showed moderate correlations and internal consistency. Only the Shame subscale was greater among younger students, but women had higher shame and guilt than men. Social desirability moderately influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
1
14
0
1
Order By: Relevance
“…The reason for the relatively lower Cronbach's α value for subscales of α and β pride could be attributed to the fewer number of items. Hasui et al (2009) showed similar results regarding the Cronbach's α for the Japanese version of TOSCA-3.…”
Section: Measurementssupporting
confidence: 80%
“…The reason for the relatively lower Cronbach's α value for subscales of α and β pride could be attributed to the fewer number of items. Hasui et al (2009) showed similar results regarding the Cronbach's α for the Japanese version of TOSCA-3.…”
Section: Measurementssupporting
confidence: 80%
“…Third, TOSCA scales can predict higher social desirability (e.g., Hasui et al, 2009), and in the present project, participants responded to morality-relevant measures in a group setting where demand characteristic could perhaps influence reactions to questionnaire items. Future research may need to explore those possibilities.…”
Section: Limitationsmentioning
confidence: 99%
“…On the other hand, Japanese investigations using university age students as the research participants have confirmed that the TOSCA Shame Scale predicts maladjustment, but they have offered little or no support for the idea that the TOSCA Guilt Scale operationalizes adjustment (Hasui et al, 2009;Uji, Kitamura, & Nagata, 2011a,b;Uji, Nagata, & Kitamura, 2012). In short, the meaning of the TOSCA Shame and Guilt Scales across cultures clearly deserves additional research attention, especially in older samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In exploring this possibility, Furukawa, Tangney, and Higashibara (2012) found that Korean, Japanese, and American children displayed differences in their average levels of shame and guilt, but linkages of these measures with other variables were similar across cultures. Japanese investigations examining university students also found that the TOSCA Shame Scale predicted maladjustment, but yielded little or no support for the contention that its guilt scale operationalized a more adaptive form of functioning (Hasui, Kitamura, Tamaki, Takahashi, Masuda, & Ozeki, 2009;Uji, Kitamura, & Nagata, 2011a, 2011bUji, Nagata, & Kitamura, 2012). In comparison to Western findings, therefore, studies in the Far East suggest that average levels of these moral affects may be different, that shame displays conceptually similar patterns of relationships with other measures, but that guilt may develop with less positive mental health implications.…”
mentioning
confidence: 96%